Current intraoperative storage and handling practices of autologous bypass conduit: A survey of the royal australasian college of surgeons - Haymet, AB; Pinto, N; Peden, S; Cohen, T; Vallely, MP; McGiffin, D; Naidoo, R; Jenkins, J; Suen, JY; Fraser, JF (Frontiers in Surgery, 2022)
During bypass surgery for peripheral arterial occlusive disease and ischaemic heart disease, autologous graft conduit including great saphenous veins and radial arteries are frequently stored in solution. Endothelial damage adversely affects the performance and patency of autologous bypass grafts, and intraoperative graft storage solutions have been shown to influence this process. The distribution of storage solutions currently used amongst Cardiothoracic and Vascular Surgeons from Australia and New Zealand is not well defined in the literature. The aim of this study was to determine current practices regarding autologous graft storage and handling amongst this cohort of surgeons, and discuss their potential relevance in the context of early graft failure. From this survey, the most frequently used storage solutions were heparinized saline for great saphenous veins, and pH-buffered solutions for radial arteries. Duration of storage was 30-45 minutes for almost half of respondents, although responses to this question were limited. Further research is required to investigate whether ischaemic endothelial injury generates a prothrombotic state, whether different storage media can alter this state, and whether this is directly associated with clinical outcomes of interest such as early graft failure.